One God – Many Religions? The Role of Negative Theology in Contemporary Interpretations of Religious Pluralism - Kałuża, Krystian (Verbum Vitae, 2023)
The article discusses the role of negative theology in contemporary interpretations of religious pluralism in an analytical and synthetic way. One of such interpretations is the pluralistic theology of religion. In view of the problems encountered due to such a way of looking at religions, a different direction of interpretation is proposed in the article. Accepting the validity of the basic intention of negative theology, the author presents a thesis that a Christian theology of religious pluralism can be based on Trinitarian theology as a kind of “matrix” of religious experience. A systematic criterion was used in the elaboration of the subsequent steps: (1) The faces of transcendence, (2) The pluralist hypothesis, (3) Via negativa, (4) The limits of negation, (5) Experience and language, (6) The nature of transcendence, (7) Toward a Trinitarian interpretation of religious pluralism. The presented model of Trinitarian interpretation of religious pluralism can be called an integrative model. It is based on the assumption that it is possible to demonstrate certain similarities between the properties of the individual Persons of the Trinity and various ideas and concepts of Ultimate Reality found in different religions.